Evolução das penas e o regime disciplinar diferenciado - Camilo, Roberta Rodrigues (2007)
The current paper analyzes the penal sanction and its evolution within the penal and procedural penal law up to the implementation of the differential, disciplinary regime, passed by Law nº. 10.792/2003, which altered article nº.52 and those that followed Law nº. 7.210/84 (Penal, Execution Law). Although, this is a relatively recent theme, it has already been object of both support and criticism. Moreover, we have analyzed the emergent circunstances that brought forth the creation of such institution. Therefore, we have investigated our Penitentiary System, which faces overcrowding problems - a great obstacle to the ressocialization of the condemned-and the bad influence of criminal groups′ leaders, many of which though imprisoned, still cause society fear. Finally, we have studied the differential, disciplinary regime in itself - that is, in its features, rules and applicability towards the Federal Constitution, for the mission of a Democratic State of Law